Family dynamics and intergenerational entrepreneurs' leadership style - Eric V. Bindah (Journal of Global Entrepreneurship Research, 2017)
Studies have shown that a family plays an important role in encouraging people to pursue an entrepreneurial career. Consequently, studies have indicated that involvement in a family role may have an effect on functioning in a non-family, work role. This study attempts to find out how behaviours, values, family structure and interpersonal interaction styles from parents can be transferred to the entrepreneur's role, as a leader, in a work environment. Specifically, this study is conducted to understand how certain parenting skills, structure, and styles enhance an entrepreneur's ability to be more efficient and effective at work. Based on the various parenting styles and family structure, propositions are made on the kind of leadership style that may arise from family dynamics. The author argues that there are various points in time where family and entrepreneurial dynamics intersect. This study argues that one very important intersection includes the entrepreneur early experiences with the family which may lead to the development of specific leadership approach at work. In this article, the author attempt to tie two streams of research together to show how entrepreneurs and their families are inextricably linked together. It is an attempt to explore the theories of family structure and parental styles to further depict these links with leadership. These areas are explored and research questions that could be empirically tested are addressed for a better understanding of how family dynamics can affect leadership. This study also explains the kind of socialization experiences that take place within the family that may lead to entrepreneurial behaviour. Such information could prove valuable to entrepreneur leaders who wish to understand their own approach towards leadership. This is important because different working environment will require specific leadership approach in order for the business to be successful. Such study would also help educational institutions to develop curriculum and training that might prove more useful in inculcating entrepreneurial values and leadership into students.
Keywords: 650; Entrepreneurs; Positive; Interrole spillover; Interrole behavioral congruence; Parental styles; Family structure; Entrepreneurship behaviour; Leadership style